Contribution of animal models to the mechanistic understanding of Alternative Pathway and Amplification Loop (AP/AL)‐driven Complement‐mediated Diseases. Issue 1 (6th October 2022) - Gibson, Beth G.; Cox, Thomas E.; Marchbank, Kevin J.
Summary: This review aimed to capture the key findings that animal models have provided around the role of the alternative pathway and amplification loop (AP/AL) in disease. Animal models, particularly mouse models, have been incredibly useful to define the role of complement and the alternative pathway in health and disease; for instance, the use of cobra venom factor and depletion of C3 provided the initial insight that complement was essential to generate an appropriate adaptive immune response. The development of knockout mice have further underlined the importance of the AP/AL in disease, with the FH knockout mouse paving the way for the first anti‐complement drugs. The impact from the development of FB, properdin, and C3 knockout mice closely follows this in terms of mechanistic understanding in disease. Indeed, our current understanding that complement plays a role in most conditions at one level or another is rooted in many of these in vivo studies. That C3, in particular, has roles beyond the obvious in innate and adaptive immunity, normal physiology, and cellular functions, with or without other recognized AP components, we would argue, only extends the reach of this arm of the complement system. Humanized mouse models also continue to play their part. Here, we argue that the animal models developed over the last few decades have truly helped define the role of the AP/AL in disease.